2020
DOI: 10.1177/0964663920946430
|View full text |Cite
|
Sign up to set email alerts
|

Securing the Future: Transformative Justice and Children ‘Born of War’

Abstract: Children born as the result of conflict related sexual violence often embody painful memories of war-affected communities. As a result, children ‘born of war’ experience abuse and neglect, social isolation and a sense of never-belonging. Existing scholarship grapples with the challenges of seeking justice for children ‘born of war’ given the complex ways their suffering is entangled with that of so many other victims. In post-conflict northern Uganda, a community-based organization composed of survivors of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…While some PKFC in the DRC reported that their mothers' attitudes towards them were characterised by ambivalence or neglect, others reflected on a sense of solidarity, emotional availability, and closeness to their mothers. Supporting pre-existing literature, we conclude that many of the family and identity-related challenges PKFC experience resemble those of CBOW in other geopolitical and historical contexts (Carpenter, 2007;Baines and Oliveira, 2021).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While some PKFC in the DRC reported that their mothers' attitudes towards them were characterised by ambivalence or neglect, others reflected on a sense of solidarity, emotional availability, and closeness to their mothers. Supporting pre-existing literature, we conclude that many of the family and identity-related challenges PKFC experience resemble those of CBOW in other geopolitical and historical contexts (Carpenter, 2007;Baines and Oliveira, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…In the mid-1990s, academics and journalists started exploring the life courses of children born of international armed conflict (e.g., children born during the two World Wars, post-war occupations, the Vietnam War and the Balkan War), creating awareness of their situations in different contexts and temporal periods (Bass, 1996;McKelvey, 1999;Grieg, 2001). Recent developments in the field draw attention to the lived experiences of children born of internal conflict, focusing predominantly on children born of conflict-related sexual violence (CRSV) including children born to mothers forcibly abducted by the Lord's Resistance Army (Apio, 2016;Denov and Cadieux Van Vliet, 2020;Baines and Oliveira, 2021), children born of forced marriage and rape by Boko Haram fighters (Matfess, 2017), and children born as a result of genocidal rape in Rwanda (Banyanga et al, 2017;Denov and Lakor, 2018;Baines and Oliveira, 2021).…”
Section: Children Born Of Warmentioning
confidence: 99%
“…PKFC are not victims of SEA in the traditional sense, but they are children born of war, who suffer from fatherlessness and the related economic and social consequences. As such they require support mechanisms that tackle their unique situation by providing them with the resources necessary to thrive as individuals (Baines and Oliveira 2020). In line with the recommendation of the Zeid report (2005), we request that assistance from the Trust Fund is extended to children born of peacekeepers whose identity is unknown or whose parents engaged in consensual sexual relations.…”
Section: Putting Victims Firstmentioning
confidence: 97%
“…Peacekeeperfathered children (PKFC), in particular, have little agency in matters of assistance since they are often too young to demand compensation themselves and have little to no information about their fathers (Blau 2016;DeLaet 2007). Moreover, their "victim status" 3 is entangled with that of their mothers, presenting a new form of victimhood that poses challenges to traditional models of justice (Baines and Oliveira 2020). In this article, we will discuss the situation of PKFC in host state communities and explore their rights under UN policies and international frameworks for support.…”
Section: Introductionmentioning
confidence: 99%
“…Especially studies on forced marriages highlighted that the vast majority (e.g., 98% in a study performed by Annan et al, 2008) of the mothers did not wish to be reconnected with the child's biological father. However, more recent studies have indicated that biological parents and clans do reconnect to support children born of war (Mutsonziwa et al, 2020;Oliveira and Baines, 2020;Baines and Oliveira, 2021) as they seek to "transform relations of violence into relations of care" (Rodriguez Di Eugenio and Baines, 2021, p. 341). We hypothesize that these differences in research outcomes could be connected to the increased need of resources and support when children born in forced captivity grow older, combined with the importance of belonging and identity for children born of war (see further).…”
Section: Influence Of Cultural and Contextual Factors On Trauma Commu...mentioning
confidence: 99%